The effects of a free-weight-based resistance training intervention on pain, squat biomechanics and MRI-defined lumbar fat infiltration and functional cross-sectional area in those with chronic low back. Issue 1 (9th November 2015) - Welch, Neil; Moran, Kieran; Antony, Joseph; Richter, Chris; Marshall, Brendan; Coyle, Joe; Falvey, Eanna; Franklyn-Miller, Andrew
Abstract : Background: Low back pain is one of the most prevalent musculoskeletal conditions in the world. Many exercise treatment options exist but few interventions have utilised free-weight resistance training. To investigate the effects of a free-weight-based resistance training intervention on pain and lumbar fat infiltration in those with chronic low back pain. Methods: Thirty participants entered the study, 11 females (age=39.6±12.4 years, height=164 cm±5.3 cm, body mass=70.9±8.2 kg, ) and 19 males (age=39.7±9.7 years, height=179±5.9 cm, body mass=86.6±15.9 kg). A 16-week, progressive, free-weight-based resistance training intervention was used. Participants completed three training sessions per week. Participants completed a Visual Analogue Pain Scale, Oswestry Disability Index and Euro-Qol V2 quality of life measure at baseline and every 4 weeks throughout the study. Three-dimensional kinematic and kinetic measures were used for biomechanical analysis of a bodyweight squat movement. Maximum strength was measured using an isometric mid-thigh pull, and lumbar paraspinal endurance was measured using a Biering-Sorensen test. Lumbar paraspinal fat infiltration was measured preintervention and postintervention using MRIs. Results: Postintervention pain, disability and quality of life were all significantly improved. In addition, there was a significant reduction in fat infiltration at the L3L4 and L4L5 levels and increase in lumbar extension time to exhaustion of 18%. Conclusions: A free-weight-based resistance training intervention can be successfully utilised to improve pain, disability and quality of life in those with low back pain.